2003
DOI: 10.1111/j.1708-8240.2003.tb00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Diagnosis of Early Enamel and Dentin Cracks Based on Microscopic Evaluation

Abstract: This article gives new guidelines for recognition, visualization, classification, and treatment of cracked teeth based on the routine use of 16x magnification. The significance of enamel cracks as they relate to dentinal cracks is detailed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 13 publications
0
71
0
1
Order By: Relevance
“…A more detailed analysis revealed that 52.1% of vertical and 42.9% of oblique cracks predisposed to higher risk of greater extent tooth damage following the removal of brackets. Previous investigations have demonstrated that horizontal micro-cracks possessed high risk of underlying pathology 21) . Thus, it was surprising to see that in our study horizontal cracks were related with low possibility of higher amount enamel defects.…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed analysis revealed that 52.1% of vertical and 42.9% of oblique cracks predisposed to higher risk of greater extent tooth damage following the removal of brackets. Previous investigations have demonstrated that horizontal micro-cracks possessed high risk of underlying pathology 21) . Thus, it was surprising to see that in our study horizontal cracks were related with low possibility of higher amount enamel defects.…”
Section: Discussionmentioning
confidence: 99%
“…23 Use of the clinical microscope makes possible the treatment of asymptomatic but structurally unsound posterior teeth. It facilitates observation of microscopic crack lines that may show minimal color contrasts against a desiccated tooth surface.…”
Section: Radiographs:-mentioning
confidence: 99%
“…Several studies showed that bleaching methods using only peroxides without light sources can cause tooth sensitivity, and this can be due to the used peroxide or one of the other ingredients in the bleaching gel [12][13][14][15][16]. On the other hand, it has been estimated that the incidence of tooth fractures or tooth cracks is to be 5 per 100 adults per year [17][18][19][20]. In fact, enamel surface cracks or craze lines, are relatively common in adult teeth [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%